تقييم الخصائص النفسية والاجتماعية لدى أطفال التوحد من وجهة نظر الوالدين بالولاية الشمالية - أحمد محمد أحمد قمر, مجذوب; الصديق محمد أحمد, محجوب (University of Eloued جامعة الوادي, 2017)
هدفت هذه الدراسة إلى الكشف عن الخصائص النفسية والاجتماعية لدى أطفال التوحد من وجهة نظر والديهم، بالولاية الشمالية – بالإضافة إلى تأثير بعض المتغيرات(النوع الاجتماعي، المستوى التعليمي، والاقتصاديّ والعمر)، المنهج المستخدم في هذه الدِّراسة هو المنهج الوصفي، ولتحقيق أهداف الدراسة أعد الباحثان أداة لقياس الخصائص النفسية والاجتماعية مكونة من (60) فقرة، موزعة على مجالين، بلغت عينة الدراسة (52) والداً ووالدة، للعام (2015)، تم اختيار عينة عن طريق المسح الشامل، تم تحليل البيانات باستخدام المتوسطات الحسابية والانحرافات المعيارية، واختبار(ت) وتحليل التباين، أظهرت النتائج: أنَّ درجة تقيم الخصائص النفسية لدى أطفال التوحد جاءت بدرجة منخفضة، كما أظهرت أنه لا توجد فروق ذات دلالة إحصائية في تقييم الخصائص النفسية والاجتماعية تُعزى لمتغيرات النوع الاجتماعي، المستوى الاقتصادي والتعليمي والعمر،وأخيراً على ضوء مناقشة النتائج توصل الباحثان إلى مجموعة من التوصيات This study aimed at investigating of Psychological and Social characteristics of children with autism from the perspectives of their parents in the Northern State of Sudan, and then to the effect of some variables, (Gender, Economic level, educational level, and age), The descriptive analytical method was used in this study, To fulfill the aim of the research, a scale of (60) items distributed among two fields has been prepared. The sample of this study consisted of (300) father and mother, year(2015), The study sample was selected through the full survey, The data is then analyzed using mean, stander deviation, T-test, ANOVA. Results showed: To assess the degree of psychological and social characteristics were low-grade, differences in the assessment of the psychological and social characteristics attributed to the variables of gender differences: the economic level, educational level, and age. Finally, in light of the study results and discussion the researcher suggested some recommendations
Assessment of psychosocial characteristics of autistic children from the perspective of parents in the northern state
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الولاية الشمالية، السودان، التوحد; Northern State, Sudan, Autism.